2017
DOI: 10.1111/ijac.12825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sintering temperature on the structural and electrochemical properties of SrFe0.5Ti0.5O3‐δ perovskite cathode

Abstract: The effects of sintering temperature on the structural and electrochemical properties of SrFe 0.5 Ti 0.5 O 3-d perovskite cathode film was investigated. For the structural properties of SrFe 0.5 Ti 0.5 O 3-d film sintered at a temperature ranging from 900-1300°C, changes in surface and cross-sectional microstructure were studied. Surface porosity and micro hardness were analyzed. The relationship of the structural properties with the electrical and electrochemical performances of the SrFe 0.5-Ti 0.5 O 3-d film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Therefore, there is always a tradeoff between the materials and the manufacturing process when determining the sintering temperature, and many studies have reported change of the electrode or cell performance outcomes according to the sintering temperature. 125,126 Surprisingly, however, none of these prior studies discussed how the sintering temperature affects the degree of Sr segregation and, thus, deterioration of electrode performance. Sintering takes place only for a short time within a few hours at higher temperatures while the operating temperature of the cell is relatively low but lasts for a very long time, possibly under a strong thermodynamic potential gradient.…”
Section: Other Contributions To Sr Segregationmentioning
confidence: 99%
“…Therefore, there is always a tradeoff between the materials and the manufacturing process when determining the sintering temperature, and many studies have reported change of the electrode or cell performance outcomes according to the sintering temperature. 125,126 Surprisingly, however, none of these prior studies discussed how the sintering temperature affects the degree of Sr segregation and, thus, deterioration of electrode performance. Sintering takes place only for a short time within a few hours at higher temperatures while the operating temperature of the cell is relatively low but lasts for a very long time, possibly under a strong thermodynamic potential gradient.…”
Section: Other Contributions To Sr Segregationmentioning
confidence: 99%
“…The film thickness also decreases as the sintering temperature increases, as demonstrated in cross-sectional micrographs. This is attributed to the densification process [35]. The densification affects the electrical conductivity and electrochemical performance of the anode through the improved Ni-Ni and BCZY-BCZY network in anode films.…”
Section: Characterisation Of Anode Filmmentioning
confidence: 99%
“…[5] Cobalt-containing perovskite oxides such as SrCo 0.8 Nb 0.1 Ta 0.1 O 3-δ have attracted immense research interest as potential IT-SOFC cathodes because of their high mixed ionic and electronic conductivities (MIECs). [19][20][21][22][23] However, because of their lower MIECs SF-based cathodes normally exhibit a lower ORR activity than Co-based cathodes in the IT range. However, the high cost of cobalt, mismatched thermal expansion coefficients (TECs) with ceria-based electrolytes, and chemical incompatibility with zirconium-based electrolytes are the major concerns for the practical application of cobalt-containing perovskites in IT-SOFCs.…”
Section: Introductionmentioning
confidence: 99%
“…at the B-site (Fe-site). [19][20][21][22][23] However, because of their lower MIECs SF-based cathodes normally exhibit a lower ORR activity than Co-based cathodes in the IT range. [24][25] To circumvent these challenges, charge imbalance could be introduced at the A-site through incorporating lowvalent cations such as alkali metals.…”
Section: Introductionmentioning
confidence: 99%